Crystal structure and lithium ionic transport behavior of Li site doped Li7La3Zr2O12. Issue 8 (July 2020) - Xiang, Xing; Liu, Yang; Chen, Fei; Yang, Wenyun; Yang, Jinbo; Ma, Xiaobai; Chen, Dongfeng; Su, Kai; Shen, Qiang; Zhang, Lianmeng
Abstract: Doping some elements on Li site of LLZO is an effective method to stabilize it as cubic phase and improve Li + conductivity. The reported possible Li site elements calculated by first principle are Be, B, Al, Fe, Zn, Ga and the Ga-doped LLZO shows the a higher conductivity than other LLZO. However, whether these elements all can stable LLZO as cubic phase are needed to be verified and the reason of Ga exhibits higher conductivity is not clear enough. In this work, all these elements are tried to be doped on Li site and the results show that the Al, or Fe, or Ga can stable LLZO as cubic phase while the others does not. The Ga-doped LLZO exhibits the highest conductivity of 1.31×10 −3 Scm -1 due to the transform of group space from Ia-3d to I-43d, shorter distances between different Li +, and Ga can improve the grain size.